Current Status and Future Direction of Immunotherapy in Hepatocellular Carcinoma: What Do the Data Suggest? - Lee, Hye Won; Cho, Kyung Joo; Park, Jun Yong (Immune network, 2020)
Most patients with hepatocellular carcinoma (HCC) are diagnosed at an advanced stage of disease. Until recently, systemic treatment options that showed survival benefits in HCC have been limited to tyrosine kinase inhibitors, antibodies targeting oncogenic signaling pathways or VEGF receptors. The HCC tumor microenvironment is characterized by a dysfunction of the immune system through multiple mechanisms, including accumulation of various immunosuppressive factors, recruitment of regulatory T cells and myeloid-derived suppressor cells, and induction of T cell exhaustion accompanied with the interaction between immune checkpoint ligands and receptors. Immune checkpoint inhibitors (ICIs) have been interfered this interaction and have altered therapeutic landscape of multiple cancer types including HCC. In this review, we discuss the use of anti-PD-1, anti-PD-L1, and anti-CTLA-4 antibodies in the treatment of advanced HCC. However, ICIs as a single agent do not benefit a significant portion of patients. Therefore, various clinical trials are exploring possible synergistic effects of combinations of different ICIs (anti-PD-1/PD-L1 and anti-CTLA-4 antibodies) or ICIs and target agents. Combinations of ICIs with locoregional therapies may also improve therapeutic responses.